THE CONCEPT OF GLOBALIZATION AND ITS ESSENCE, CONFLICTS - Kudratillo Yunisov (Journals Park Publishing, 2023)
In the article, the concept of globalization and its essence, modern forms of globalization, processes of globalization, conflicts are covered in detail with the help of information from scientific literature.
Keywords: globalization, process, conflict, form, essence, states, nations.